For Talaqqi Method: Learning the Qur'an - Hapsari , Nadya Ayu; Rohmah, Siti; Sa’diyah, Sa’diyah; Busahdiar, Busahdiar; Syaidah, Khasnah (MISYKAT AL-ANWAR JURNAL KAJIAN ISLAM DAN MASYARAKAT, 2025)
For some people, memorizing the Qur'an is easy. However, many find memorizing the Qur'an difficult. Especially for children who are still in the development and play stage. One of the factors that influences children's difficulty in memorizing the Qur'an is when a friend disturbs other friends while memorizing the Qur'an. This makes the class not conducive so that teaching and learning activities are disrupted. The purpose of this study was to determine the use of the Talaqqi method in learning the Qur'an at SDIT Buah Hati Kramatjati, East Jakarta. This study uses a qualitative approach. The main sources in this study were the Qur'an teachers and students of SDIT Buah Hati Kramatjati, while the secondary sources were journals, books, e-books, and so on that were directly related to this study. Data collection techniques used interviews, observations, and document examinations. The examination of the validity of this research data used credibility by extending observations, increasing perseverance in research and triangulation. The findings of the study indicate that 1) Planning the learning of the Qur'an with the Talaqqi method using a syllabus and lesson plan is very important to ensure that learning activities run in a structured, organized manner and achieve the goals that have been set. 2) The application of the Talaqqi method has the advantage of a more personal approach and focuses on the quality of student reading. Such as in a class with 25 students, teachers can control around 8 to 9 students more intensively. This method allows teachers to provide direct guidance. During the memorization process, teachers actively provide evaluation and correction of students' reading. 3) The results of the application of the Talaqqi method have proven effective from researchers conducting observations in class. Students read the Qur'an properly and correctly after the teacher gave examples of the pronunciation of the letters of the Qur'an also accompanied by the rules of reading, so that errors in the pronunciation of hijaiyah letters (makharijul huruf) or tajwid rules are reduced because intensive guidance is carried out through Talaqqi.